CALANOID COPEPODS OF THE GENUS CENTROPAGES AND ITS SPECIES-GROUP FROM INDONESIAN WATERS - Mulyadi, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
The marine copepods of the genus Centropages form a very important component of tropical marine ecosys-tem, but are poorly known. In a continuing study of the copepods of Indonesian coastal waters, eight species of Centropages were collected from 11 sites during 1996-2006. Four out of five previously known species i.e., C. calaninus (Dana, 1849); C. furcatus (Dana, 1849); C. gracilis (Dana, 1849); C. orsini Giesbrecht, 1896, except C. elongatus Giesbrecht, 1869 have been recorded. Four species i.e., C. brevifurcus Shen and Lee, 1963; C. dorsispinatus Thompson and Scott, 1903; C. sinensis Chen and Zhang, 1965; and C. tenuiremis Thompson and Scott, 1903, are new records for the area.